Diagnosis and management of oral lesions and conditions in the newborn - Willie F.P. van Heerden; Andre W. van Zyl (South African Family Practice)
Infants frequently present with oral lesions and conditions that may lead to anxiety among parents. The most common lesions and conditions include natal and neonatal teeth, the different oral mucosal cysts of the newborn, ankyloglossia and congenital epulis of the gingiva. The diagnostic features and management principles of these lesions are discussed in order for healthcare workers to provide proper care and counselling to patients and parents.